POTENTIAL ANTIBACTERIAL ACTIVITY OF Sapindus rarak DC FRUIT AGAINST ESBL (EXTENDED SPECTRUM BETA LACTAMASE) PRODUCING Escherichia coli: IN SILICO AND IN VITRO STUDIES - Nugraha, Fajar; Kurniawan, Hadi; IH, Hariyanto; Fajriaty, Inarah; Nurbaeti, Siti Nani (BRIN Publishing (Penerbit BRIN), 2025)
The increasing Antimicrobial Resistance (AMR) drives the need of new antibacteria as drug candidate to eradicate resistant bacteria such as ESBL (Extended Spectrum Beta-Lactamase) producing Escherichia coli. Extract and fraction of Sapindus rarak fruit contains numerous saponin compounds, which exert potential antibacterial effect by binding to the bacterial cell membrane. The purpose of this research is to analyze and evaluate Sapindus rarak fruit extract and fraction antibacterial effects through in silico and in vitro approach. Molecular docking is conducted to identified compounds contained in Sapindus rarak fruit against Penicillin Binding Protein (PDB ID: 6NTZ) using Autodock Tools. Antibacterial testing of Sapindus rarak fruit extract and fraction is also conducted with disc diffusion and microdilution. In silico docking study resulted in potential activity from raraoside A and rarasaponin V, which showed affinity tinggi through their binding energy whilst interacting with the active site of the receptor protein. No inhibition zone was detected on extract and fraction, yet lowest minimum inhibition concentration (MIC) was detected at 2.5×104μg/mL on water and n-hexane fraction Sapindus rarak fruit ethanol extract. This weak antibacterial effect tends to happen to crude extract than to compound isolates. Hence, Sapindus rarak fruit fraction exhibits weak antibacterial effect on ESBL producing E. coli, but certain isolates might be potential to be further researched. Sapindus rarak fruit isolates such as raraoside A and rarasaponin V is potential to solve antimicrobial resistance by acting as a plant based antibiotic.